Review Paper : Occurrence of wheat blast in Bangladesh and its implications for South Asian wheat production - Chowdhury, Apurba Kumar; Saharan, Mahender Singh; Aggrawal, Rashmi; Malaker, Paritosh Kumar; Barma, N. C. D.; Tiwari, T. P.; Duveiller5, Etienne; Singh, Pawan Kumar; Srivastava, Amit Kumar; Sonder6, Kai; Singh, Ravi Prakash; Braun, Hans Joachim; et al. (The Indian Journal of Genetics and Plant Breeding, 2017)
The first recorded occurrence in Asia of wheat blast caused by Magnaporthe oryzae, pathotype Triticum (synonym Pyricularia oryzae) occurred in Bangladesh in March 2016. Crop losses of up to 90% have been reported, with latesown wheat suffering particularly badly. The emergence of this disease has raised concern in neighboring countries where wheat represents a significant crop, most notably in India and Nepal. The existence of effective genetic resistance is in doubt, so for the moment the sole means of control is via the application of fungicides and adoption of beneficial cultural practices. The disease has been endemic in parts of South America for the last 30 years, so only a coordinated program of research and development has the potential to deliver rapid progress in combating the disease. In addition to evaluating and deploying genetic resistance and applying fungicides on an occasional basis, some control could be made possible by altering current crop rotation practice and/or manipulating the sowing time to promote disease escape.